c-Fos immunoreactivity in prefrontal, basal ganglia and limbic areas of the rat brain after central and peripheral administration of ethanol and its metabolite acetaldehyde - Segovia, Kristen N.; Vontell, Regina; López-Cruz, Laura; Salamone, John D.; Correa, Merce (Frontiers in Behavioral Neuroscience, 2013)
Considerable evidence indicates that the metabolite of ethanol (EtOH), acetaldehyde, is biologically active. Acetaldehyde can be formed from EtOH peripherally mainly by alcohol dehydrogenase, and also centrally by catalase. EtOH and acetaldehyde show differences in their behavioral effects depending upon the route of administration. In terms of their effects on motor activity and motivated behaviors, when administered peripherally acetaldehyde tends to be more potent than EtOH but shows very similar potency administered centrally. Since dopamine (DA) rich areas have an important role in regulating both motor activity and motivation, the present studies were undertaken to compare the effects of central (intraventricular, ICV) and peripheral (intraperitoneal, IP) administration of EtOH and acetaldehyde on a cellular marker of brain activity, c-Fos immunoreactivity, in DA innervated areas. Male Sprague-Dawley rats received an IP injection of vehicle, EtOH (0.5 or 2.5 g/kg) or acetaldehyde (0.1 or 0.5 g/kg) or an ICV injection of vehicle, EtOH or acetaldehyde (2.8 or 14.0 µmoles). IP administration of EtOH minimally induced c-Fos in some regions of the prefrontal cortex and basal ganglia, mainly at the low dose (0.5 g/kg), while IP acetaldehyde induced c-Fos in virtually all the structures studied at both doses. Acetaldehyde administered centrally increased c-Fos in all areas studied, a pattern that was very similar to EtOH. Thus, IP administered acetaldehyde was more efficacious than EtOH at inducing c-Fos expression. However, the general pattern of c-Fos induction promoted by ICV EtOH and acetaldehyde was similar. These results are consistent with the pattern observed in behavioral studies in which both substances produced the same magnitude of effect when injected centrally, and produced differences in potency after peripheral administration.